2017
DOI: 10.3390/nu9101067
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentration of Leptin in Pregnant Adolescents Correlated with Gestational Weight Gain, Postpartum Weight Retention and Newborn Weight/Length

Abstract: Introduction: Gestational weight gain is an important modifiable factor known to influence fetal outcomes including birth weight and adiposity. Leptin is normally correlated with adiposity and is also known to increase throughout pregnancy, as the placenta becomes a source of leptin synthesis. Several studies have reported positive correlations between cord blood leptin level and either birthweight or size for gestational age, as well as body mass index (BMI). Objective: To determine the correlation of prenata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 33 publications
3
33
1
5
Order By: Relevance
“…In this study, we targeted LEP, CSHL1, ELA, activin A, sFlt-1, and PlGF as biomarker candidates for estimating GA and identifying an impending onset of PE. These 6 proteins are not only associated with the placenta and reflect placental growth [8,[30][31][32]; but also because we found that CSHL1 and PlGF were highly correlated to GA from 10 to 30 weeks of pregnancy by our longitudinal quantitative analysis [2] and that the levels of these proteins differ in women with PE compared with women with normal pregnancies. The predictive value of sFlt-1 and PlGF in PE has been validated by a number of studies [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this study, we targeted LEP, CSHL1, ELA, activin A, sFlt-1, and PlGF as biomarker candidates for estimating GA and identifying an impending onset of PE. These 6 proteins are not only associated with the placenta and reflect placental growth [8,[30][31][32]; but also because we found that CSHL1 and PlGF were highly correlated to GA from 10 to 30 weeks of pregnancy by our longitudinal quantitative analysis [2] and that the levels of these proteins differ in women with PE compared with women with normal pregnancies. The predictive value of sFlt-1 and PlGF in PE has been validated by a number of studies [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 93%
“…These findings are in line with our longitudinal biomarker trending analyses (Fig 3). Since there was a positive association [8] between maternal serum LEP concentrations and body…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Chorionic somatomammotropin hormone like 1 (CSHL1; also called 55 human placental lactogen) is selectively expressed in placental villi with an important role in 56 regulating placental growth. Leptin (LEP) has been suggested to be involved in placental and 57 fetal growth [8]. The relationship between LEP and PE has been discussed in a few studies [9-58 17].…”
mentioning
confidence: 99%
“…Лептин -гормон, який синтезується в основному адипоцитами, передає інформацію щодо маси тіла в гіпоталамус, знижує апетит та відчуття голоду і споживання їжі. Даний гормон контролює масу жирової тканини шляхом стимуляції обміну ліпідів (підвищує швидкість ліполізу, зменшує вміст тригліцеридів в жировій тканині, печінці, скелетних м'язах та підшлунковій залозі, посилює термогенез) і є ін дикатором запасу енергії в організмі [4]. Під час вагітності лептин додатково продукується плацентою.…”
unclassified